Estudo laboratorial da viabilidade do uso de fibras de coco em misturas asfálticas do tipo SMA - Vale, Aline Colares do (2007)
The technology of asphalt materials and mixtures evolves very in these last three decades in the Europe and the North America. To the rolling layer, it comes growing the use in developed countries of more resistant and more durable asphalt mixtures, being that some of these solutions involve the job of discontinous graduation, as the SMA (Stone Matrix Asphalt). The main objective of this research presents the evaluation of the potential use of coconut fibers in the mixture SMA with different aggregate gradations using both the Marshall and Superpave (level 1) desing method. The differences between these two design methods are: (i) theoretical maximum specific gravity (Gmm) determination; (ii) compaction method and (iii) short-term aging of the mixtures. It was selected to this research dense mixtures with 4% air voids. The Gmm was determined indirectly from the mixture composition and the relative densities of the constituents of the mixes, and through the uses of a vacuum pump (Rice method). Short-term aging was considered just in the Superpave design, with 2 hours in the oven at the compaction temperature. The design results showed the same optimum asphalt content for Marshall and Superpave mixtures. The mechanical behavior of the mixtures was evaluated by: the indirect tensile strenght, resilient modulus, fatigue life (stress controlled) and resistance to moisture damage. The results show that the coconut fibers meet current requirements. This analysis of the viability of the use of the local fiber is important for the Northeast region, due to valuation of regional material e, also, for economically viable when being compared with the fiber of cellulose due its abundance in the region.